Competitive Strategy of PT. XYZ Through SWOT Analysis in the Digital Era - Ulyah Agistia Putri; Hapzi Ali (Dinasti Publisher, 2025)
This study aims to formulate an effective competitive strategy for PT. XYZ in facing industry challenges in the digital era. The object of the research is PT. XYZ, a furniture company that manufactures sofas and mattresses for the domestic and export markets, is currently facing competitive pressure from the growing number of competitors and the shift in consumer preferences to digital platforms. The method used in this study is qualitative descriptive with a case study approach, through data collection from literature studies and observation of the company's digital business activities. The analysis is carried out using SWOT tools to identify internal factors in the form of strengths and weaknesses, as well as external factors in the form of opportunities and threats that affect the company's competitiveness. The results of the study show that PT. XYZ has strength in product quality and production capacity, but is still weak in terms of digitalization and online marketing. Opportunities arise from the development of e-commerce and the increasing demand for quality household products, while threats come from more agile digital competitors and rapid changes in consumer trends. The proposed strategies include increasing the digitization of business processes, strengthening brand identity through digital media, and developing innovative products based on digital market trends. This strategy is expected to be able to strengthen the competitive position of PT. XYZ in both national and global markets.